Hepatitis B Infection in Pregnancy-Experience at a Tertiary Care Centre of North India - Malhotra, Vani; Malhotra, Parveen; Bhuriya, Vandana; Pahuja, Isha; Nanda, Smiti; Chauhan, Meenakshi; Sangwan, Neetu (Journal of Hematology Research, 2017)
Objectives: To investigate the Seroprevalence of hepatitis B surface antigen in pregnant women and managing chronic HBV infection in pregnant women for preventing mother to child transmission. Methods: Fifteen thousand pregnant women were evaluated using history, examination and test for serum HbsAg and who were found to be HbsAg positive underwent liver function tests, HbeAg and HBV DNA analysis by Polymerase Chain Reaction (PCR). Results: out of fifteen thousand (15000) women, 52 women tested positive for HbsAg. Of these, 8(15.38%) presented with acute hepatitis and 44(84.6%) were asymptomatic carriers. The highest HbsAg positivity was seen in age group of 20-25 years and maximum women were multiparous (67.23%). Assessment of risk factors revealed history of tattooing in 22 women (42.3%). Out of 52 women, 12 patients tested positive for HbeAg and their DNA tires were more than one Lakh copies/ml. Forty six women(88.4%) delivered vaginally and rest 6(11.5%) underwent cesarean section which was mainly done for obstetric indications. All the babies born received immunoglobulin and first dose of HBV vaccine within 12 hours of birth. Conclusion: Seroprevalence of HbsAg in antenatal women was found to be 0.34%.